Recent developments on the magnetic and electrical transport properties of FeRh- and Rh-based heterostructures. (2nd February 2022) - Zhu, Xiaoyan; Xu, Yang; Cao, Cuimei; Shang, Tian; Xie, Yali; Zhan, Qingfeng
Abstract: It is fascinating how the binary alloy FeRh has been the subject of a vast number of studies almost solely for a single-phase transition. This is, however, reasonable, considering how various degrees of freedom are intertwined around this phase transition. Furthermore, the tunability of this phase transition—the large response to tuning parameters, such as electric field and strain—endows FeRh huge potential in applications. Compared to the bulk counterpart, FeRh in the thin-film form is superior in many aspects: materials in thin-film form are often more technologically relevant in the first place; in addition, the substrates add extra dimensions to the tunability, especially when the substrate itself is multiferroic. Here we review recent developments on the magnetic and transport properties of heterostructures based on FeRh and its end-member Rh, with the latter providing a new route to exploiting spin–orbit interactions in functional spintronic heterostructures other than the more often employed 5 d metals. The methods utilized in the investigation of the physical properties in these systems, and the design principles employed in the engineering thereof may conceivably be extended to similar phase transitions to other magnetic materials.